Slope Finder – A Distance Measure for DTW based Isolated Word Speech Recognition (International Journal of Engineering and Computer Science, 2013)
Speech can be recognized by machine using many algorithms like Dynamic Time Warping, Hidden Markov Model, Artificial Neural Networks etc.,. In this paper, an overview of Dynamic Time Warping and the various distance metrics used to measure the spectral distance are discussed. A new distance metric is proposed which reduces the computational complexit